Larynx Replacement by a Device after Total Laryngectomy: Initial Clinical Experience, Future Steps. (2nd September 2014) - Dupret‐Bories, Agnès; Schultz, Philippe; Vrana, Nihal Engin; Hémar, Patrick; Vautier, Dominique; Lavalle, Philippe; Debry, Christian
Abstract : Objectives: To present the first cases of laryngeal rehabilitation by an artificial larynx performed after a total laryngectomy. The prosthesis aims at proposing an alternative to laryngeal transplantations and to techniques of tissular engineering and/or transplants by free fragments, used essentially in tracheal reconstructions. Methods: The artificial larynx was developed thanks to fundamental biomaterial research and long‐term animal experiments. The insertion is a 2‐stage procedure. The first step, performed immediately after the total laryngectomy, consists of connecting the trachea with a hollow titanium tube. After a 6‐week period of healing, or 3 months after radiotherapy, a swallowing valve is fixed over the integrated titanium tube (second step). Results: Four patients have been treated (2 whole prosthesis, 2 partial prostheses) from June to December 2012. Two patients were able to talk in a whispering fashion while the tracheostomy was temporarily closed; their functioning in the relevant postoperative problem areas, such as swallowing, breathing, and smelling were significantly improved. Conclusions: Our clinical trials demonstrated that a temporary closure of the tracheostomy opening can be achieved. Potential improvements of this larynx replacement open real perspectives of complete rehabilitation after total laryngectomy. The artificial larynx, which does not require immune‐suppressor treatment, would avoid the definitive tracheostomy, considered by most patients as a loss of physical and psychological integrity.